2017
DOI: 10.1016/j.joca.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise preconditioning enhances mesenchymal stem cell-based cartilage regeneration through epigenetic modification

Abstract: These findings indicated a feasible method to obtain a cell population with high survivability and chondrogenic commitment for the treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Until now, the etiology and pathophysiology of OA have not been well documented. Various treatments, such as cellular therapies (Fu et al, 2014;Lee and Wang, 2017;Lin et al, 2017;Teo et al, 2019;Xu et al, 2019), administration of certain drugs or chemicals (Zhang et al, 2016(Zhang et al, , 2019Yao et al, 2019), therapeutic surgeries (Chen Y. et al, 2015), and biofabrication approach (Tatman et al, 2015;Onofrillo et al, 2018;Lee et al, 2019), have been intensely studied and tested in various preclinical studies and clinical trials during recent decades (Lee and Wang, 2017;Zhang et al, 2019). However, several hurdles are required to be addressed for therapeutic optimization before clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the etiology and pathophysiology of OA have not been well documented. Various treatments, such as cellular therapies (Fu et al, 2014;Lee and Wang, 2017;Lin et al, 2017;Teo et al, 2019;Xu et al, 2019), administration of certain drugs or chemicals (Zhang et al, 2016(Zhang et al, , 2019Yao et al, 2019), therapeutic surgeries (Chen Y. et al, 2015), and biofabrication approach (Tatman et al, 2015;Onofrillo et al, 2018;Lee et al, 2019), have been intensely studied and tested in various preclinical studies and clinical trials during recent decades (Lee and Wang, 2017;Zhang et al, 2019). However, several hurdles are required to be addressed for therapeutic optimization before clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the dedifferentiation-reprogramming method was also effective in chondrogenesis. According to Li et al 129 , rat MSCs in vitro that are incubated in chondrogenic induction medium undergo chondrogenesis and then are allowed to grow and subculture in growth medium to expand and dedifferentiate (Fig. 4b).…”
Section: Dedifferentiation In Diseases (As a Pathological Factor)mentioning
confidence: 99%
“… a Immunofluorescence staining revealed the preferential neuronal differentiation of De-MSCs, as evidenced by the higher expression of neuronal markers, including neurofilament-M (NF-M) and microtubule-associated protein 2 (MAP2) (used with permission from John Wiley and Sons/Hsiao et al 127 ). b Histology and immunohistochemistry revealed that the M-MSC group exhibited a greater therapeutic effect on OA, as evidenced by the increased ECM deposition, increased number of GFP-positive cells, and reduction in MMP-13 expression 129 (Copyright 2017, with permission from Elsevier). …”
Section: Introductionmentioning
confidence: 99%
“…These results implied that the regenerated cartilages seem to have a memory of their original form. Although the underlying mechanisms were still unclear, it could be speculated that the epigenetic regulation might play an important role in determining the ultimate fate of regenerated cartilage type (Carlson et al, ; Duan, Liang, Ma, Zhu, & Wang, ; Lin et al, ). Nevertheless, all of the in vivo regenerated cartilage expressed noncartilage‐specific ECM, such as collagen type I, which might be a result of the dedifferentiation status of expanded chondrocytes before used for cartilage regeneration, transforming growth factor‐beta in the culture medium, and the regulation of the subcutaneous micro‐environment.…”
Section: Discussionmentioning
confidence: 99%